Radicalizing the Digital Humanities: Reimagining Environmental Justice Research and Teaching - Ruiz, Stevie; Areguin, Maira; Estrada, Eduardo; Jimenez, Jesus; Lopez, Diane; Sanchez, Karla; Valenzuela, Janet (Radical Teacher, 2017)
This article is about collaboration between students and professors on environmental justice research in digital humanities labs. A collective of university students and their professor investigated digital archives pertaining to the Civilian Conservation Corps (CCC) using mind mapping software called XMind. Our purpose was to enable and organize findings on segregation and discrimination within CCC camps. The impact this research had on students who came from interdisciplinary backgrounds was exposure to the use of technological resources in the context of an increasing need to use technology to preserve historical archives, carry out research, and make connections to other research on the topic of environmental justice. Interdisciplinary in their approach, students used mind mapping software to organize data visually. Lab members recognized that visualization of information allowed students to think about how to organize information using methods of historical analysis. It allowed them to organize information about Chicana/o participation in CCC camps according to social categories such as race, class, and gender. As a collective of students and faculty, we are enthusiastic about sharing our journey with digital humanities software so that other teachers may experiment with their own attempts at radicalizing the digital humanities.